Methodological quality and synthesis of case series and case reports. Issue 2 (2nd February 2018) - Murad, Mohammad Hassan; Sultan, Shahnaz; Haffar, Samir; Bazerbachi, Fateh
Abstract : Case reports and case series are uncontrolled study designs known for increased risk of bias but have profoundly influenced the medical literature and continue to advance our knowledge. In this guide, we present a framework for appraisal, synthesis and application of evidence derived from case reports and case series. We propose a tool to evaluate the methodological quality of case reports and case series based on the domains of selection, ascertainment, causality and reporting and provide signalling questions to aid evidence-based practitioners and systematic reviewers in their assessment. We suggest using evidence derived from case reports and case series to inform decision-making when no other higher level of evidence is available.